Analysis of Green Campus Implementation Based on the UI GreenMetric Indicators at Kalimantan Institute of Technology - Tiara Rukmaya Dewi; Muhamad Nur Ibnu Luthfi Saud; Hermawan Juliansyah (P3KM Politeknik Pertanian Negeri Samarinda, 2026)
UI GreenMetric World University Rankings is one of the sustainability assessment instruments used to evaluate green campus performance through six main categories: Setting and Infrastructure, Energy and Climate Change, Waste, Water, Transportation, and Education and Research. This study aims to analyze the implementation of green campus at Institut Teknologi Kalimantan based on the 2025 UI GreenMetric indicators. This study employed a quantitative descriptive method with a data analysis approach using data obtained from the 2025 UI GreenMetric fact file, the UI GreenMetric questionnaire data of Institut Teknologi Kalimantan, the 2025 UI GreenMetric guideline, and institutional achievement documents. The results show that Institut Teknologi Kalimantan obtained a total score of 3.322,5 out of 10.000 points, equivalent to 33.23%. The Setting and Infrastructure category obtained 705 points, Energy and Climate Change 625 points, Waste 500 points, Water 387,5 points, Transportation 360 points, and Education and Research 745 points. The highest achievement was found in the Setting and Infrastructure category, while the lowest achievement was found in the Transportation category. These findings indicate that Institut Teknologi Kalimantan has strong spatial potential as a green campus, but still requires improvement in renewable energy, green building implementation, waste management, water management, sustainable transportation, sustainability reporting, and data-based governance.